Captain America. The Winter Soldier [videorecording (Blu-Ray)] - Evans, Chris, 1981-; Jackson, Samuel L.; Johansson, Scarlett, 1984-; Redford, Robert; Stan, Sebastian, 1982- (Buena Vista Home Entertainment, 2017)
Steve Rogers, aka Captain America, is living quietly in Washington, D.C. trying to adjust to the modern world. But when a S.H.I.E.L.D. colleague comes under attack, Steve becomes embroiled in a web of intrigue that threatens to put the world at risk. Joining forces with the Black Widow, Captain America struggles to expose the ever-widening conspiracy while fighting off professional assassins sent to silence him at every turn.